Lambda red mediated gap repair utilizes a novel replicative intermediate in Escherichia coli. - Thimma R Reddy; Léna M S Fevat; Sarah E Munson; A Francis Stewart; Shaun M Cowley (PLoS ONE)
The lambda phage Red recombination system can mediate efficient homologous recombination in Escherichia coli, which is the basis of the DNA engineering technique termed recombineering. Red mediated insertion of DNA requires DNA replication, involves a single-stranded DNA intermediate and is more efficient on the lagging strand of the replication fork. Lagging strand recombination has also been postulated to explain the Red mediated repair of gapped plasmids by an Okazaki fragment gap filling model. Here, we demonstrate that gap repair involves a different strand independent mechanism. Gap repair assays examining the strand asymmetry of recombination did not show a lagging strand bias. Directly testing an ssDNA plasmid showed lagging strand recombination is possible but dsDNA plasmids did not employ this mechanism. Insertional recombination combined with gap repair also did not demonstrate preferential lagging strand bias, supporting a different gap repair mechanism. The predominant recombination route involved concerted insertion and subcloning though other routes also operated at lower frequencies. Simultaneous insertion of DNA resulted in modification of both strands and was unaffected by mutations to DNA polymerase I, responsible for Okazaki fragment maturation. The lower efficiency of an alternate Red mediated ends-in recombination pathway and the apparent lack of a Holliday junction intermediate suggested that gap repair does not involve a different Red recombination pathway. Our results may be explained by a novel replicative intermediate in gap repair that does not involve a replication fork. We exploited these observations by developing a new recombineering application based on concerted insertion and gap repair, termed SPI (subcloning plus insertion). SPI selected against empty vector background and selected for correct gap repair recombinants. We used SPI to simultaneously insert up to four different gene cassettes in a single recombineering reaction. Consequently, our findings have important implications for the understanding of E. coli replication and Red recombination.